On demand synthesis of hollow fullerene nanostructures - Han, Fei (2019)
Hollow nanostructures are widely used in chemistry, materials, bioscience, and medicine, but their fabrication remains a great challenge. In particular, there is no effective strategy for their assembly and interconnection. We bring pottery, the oldest and simplest method of fabricating hollow containers, into the nanoscale. By exploiting the liquid nature of the xylene template, fullerene hollow nanostructures of tailored shapes, such as bowls, bottles, and cucurbits, are readily synthesized. The liquid templates permit stepwise and versatile manipulation and hence, modular assembly of nodes and junctions leads to interconnected hollow systems. As a proof-of-concept, we create multi-compartment nano-containers, with different nanoparticles isolated in the separate pockets. This methodology expands the synthetic freedom for hollow nanostructures, building a bridge from isolated hollow units to interconnected hollow systems.